Immune Checkpoint and Telomerase Crosstalk Is Mediated by miRNA-138 in Bladder Cancer - El Ahanidi, Hajar; El Azzouzi, Meryem; Hafidi Alaoui, Chaimae; Tetou, Mohammed; Bensaid, Mounia; Chaoui, Imane; Benbacer, Laila; Hassan, Ilias; Oukabli, Mohamed; Michaud, Katarzyna; Ameur, Ahmed; Al Bouzidi, Abderrahmane; et al. (Frontiers in Oncology, 2022)
Background Tumor recurrence and progression in non-muscle invasive bladder cancer (NMIBC), therapy failure, and severe side effects in muscle invasive bladder cancer (MIBC) are the major challenges in the clinical management of bladder cancer (BC). Here, we identify new molecular targetable signatures to improve BC patients’ stratification and the outcome of current immunotherapies. Material and Methods In a prospective cohort of 70 BC patients, we assessed the genetic and molecular regulation of TERT in maintaining telomere length in parallel to immune checkpoint and microRNA expression. Results TERT was undetectable in healthy bladder tissues but upregulated in invasive BC stages and high tumor grade. Its expression was linked with the combined effect of the C250T mutation and THOR hypermethylation, associated with progressing tumors and maintaining of telomere length. In the same cohort, PD-L1 scored highest in NMIBC, while PD-L2 was upregulated in MIBC. We also show that miR-100-5p and 138-5p were highly expressed in healthy bladder specimens and cell line, while expression decreased in the BC tissues and BC cell lines. In line with the binding prediction for these miRNAs on target genes, miRs 100-5p and 138-5p expression strongly inverse correlated with TERT, PD-L1, and PD-L2 expression, but not PD1. Conclusion We identify a loop involving TERT, PD1-ligands, and miR-138-5p in BC, that might represent not only a useful biomarker for improved diagnosis and patients’ stratification but also as a promising axis that might be therapeutically targeted in situ.